Wspomaganie dydaktyki matematyki narzędziami informatyki - Kopańska-Bródka, Donata (Information technology supporting mathematical education, 2010)
The goals of mathematical education in universities of economics and business schools are discussed. These goals are compared with the student‘s profile and their oppor-tunities for learning mathematics. Information technology is effective in learning and teaching mathematics. Using multiple media together offers enormous opportunities for making learning mathematics meaningful and effective. Supporting the teaching of infor-matics tools is necessary condition of improving students‘ mathematical activity
Didactics of Mathematics, 2010, Nr 7 (11), s. 49-58
Keywords: mathematics education; multimedia in education